2006
DOI: 10.1080/10611860600566548
|View full text |Cite
|
Sign up to set email alerts
|

A sustained release dosage form of acyclovir for buccal application: An experimental study in dogs

Abstract: Acyclovir is an antiviral agent and it has been particularly used for the treatment of herpes simplex infections. The treatment of infection in the oral cavity is often difficult, because of insufficient drug concentration in saliva when acyclovir is administered via the oral route in conventional tablet form for systemic uptake. Therefore, it was aimed to prepare a tablet for buccal administration and to investigate its effectiveness by performing in vitro and in vivo experiments.The solubility (1.559-4.584) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…59 Acyclovir is bioavailable when administered orally to dogs and is widely distributed within tissues; however, target plasma concentrations and effective dosages for CHV infection are currently unknown. [57][58][59] Acyclovir toxicosis resultant from accidental ingestion is reported in dogs with dosages as low as 40 mg/kg and the routine clinical use of this, and other systemic antiviral medications, in dogs for CHV infection requires further investigation of safety and efficacy. 60 The canine pharmacokinetics of newer-generation antiherpesviral drugs, including famciclovir, are reported.…”
Section: Therapeuticsmentioning
confidence: 99%
“…59 Acyclovir is bioavailable when administered orally to dogs and is widely distributed within tissues; however, target plasma concentrations and effective dosages for CHV infection are currently unknown. [57][58][59] Acyclovir toxicosis resultant from accidental ingestion is reported in dogs with dosages as low as 40 mg/kg and the routine clinical use of this, and other systemic antiviral medications, in dogs for CHV infection requires further investigation of safety and efficacy. 60 The canine pharmacokinetics of newer-generation antiherpesviral drugs, including famciclovir, are reported.…”
Section: Therapeuticsmentioning
confidence: 99%
“…Several studies have been reported wherein acyclovir has been formulated as buccal tablets or films [8,9]. However, the mucoadhesive buccal tablets of acyclovir currently in the market have been approved for the topical or local delivery of the drug in the oral cavity for the treatment of herpes labialis and is expected to be minimally absorbed through the oral mucosa.…”
Section: Introductionmentioning
confidence: 99%